Penerapan Model Pembelajaran Double Loop Problem Solving (DLPS) terhadap Kemampuan Pemecahan Masalah Matematis Siswa SMP - Adlyani, Hafidz; Duskri, M.; Susanti, Susanti (Mathieu : Journal of Mathematics Education and Learning, 2026)
This study aims to determine the effect of the Double Loop Problem Solving (DLPS) learning model on students' mathematical problem system abilities. The method used is a quasi-experimental design with the Control Group Post Test Design. The sample in this study was taken using total sampling because the researcher used the entire population as the research sample. The results showed that: (1) the effect of the Double Loop Problem Solving (DLPS) learning model on the students' problem management ability. It can be concluded that the Double Loop Problem Solving (DLPS) learning model has an effect on students' mathematical problem abilities. (2) Based on the independent sample t test, the value of tcount> ttable or 6.59> 1.69. So the problem is that the ability to solve mathematical problems of students who are taught with the Double Loop Problem Solving (DLPS) learning model is better than the management skills of students who are taught using conventional learning.